Leaf economic strategies drive global variation in phosphorus stimulation of terrestrial plant production - Nan Yang; Constantin M. Zohner; Thomas W. Crowther; Jiguang Feng; Jin Wu; Xinli Chen; Wenxuan Han; Benjamin D. Stocker; Dafeng Hui; Laurent Augusto; Kai Yue; Enqing Hou; et al. (Nature Communications)
Abstract Plant biomass and its allocation are fundamental for understanding biospheric matter production. However, the impacts of atmospheric phosphorus (P) deposition on species-specific biomass and its allocation in global terrestrial plants remain unclear. By synthesizing 5548 observations of plant biomass and its allocation related to P addition worldwide, we find that P addition increases plant biomass by an average of 35% globally. This increase varies across plant functional groups, with stronger responses in deciduous (45%), C3 (36%), and N2-fixing plants (54%) than in evergreen (28%), C4 (19%), and non-N2-fixing plants (31%), respectively. Plants possessing traits indicative of an acquisitive strategy, such as higher nutrient concentrations and specific leaf area, faster photosynthetic rates and shorter leaf lifespan, are particularly responsive to P addition. Furthermore, P addition promotes a greater allocation of biomass to aboveground than belowground organs, resulting in a 5% decrease in root-to-shoot ratio. Our findings provide global-scale quantifications of how P addition regulates biomass accumulation and allocation strategies in terrestrial plants, offering critical insights for predicting the response of terrestrial carbon storage to rising atmospheric P deposition.